Corporate governance in Singapore recent developments for the next millennium - Teen, Mak Yuen; Phan, Phillip H. (The Philippine Review of Business and Economics, 2000)
This paper surveys the regulatory and structural environment as it relates to corporate governance in Singapore, and present empirical evidence on corporate governance practices in areas such as ownership structure, disclosure, board and directors, the use of share option schemes, and the impact of government corporate ownership. It reviews corporate governance reforms that have been implemented or proposed, and assesses their likely impact on future corporate governance practices in Singapore. Remaining concerns with the future of corporate governance in Singapore are also discussed.